INTERCULTURAL SENSITIVITY IN ENGLISH DEPARTMENT STUDENTS OF AN INDONESIAN HIGHER EDUCATION INSTITUTION - Dollah, Syarifuddin; Abduh, Amirullah; Talib, Ahmad (Universitas Negeri Makassar, 2017)
This study aimed at identifying intercultural sensitivity elements perceived by English department students in an Indonesian university. Broadly, this study used mix-methods: quantitative and qualitative data. Quantitative data were obtained through questionnaires. The questionnaires were sent to 100 participants and followed by semi-structured interview of 10 participants. For this paper, only quantitative data were used. The findings show that there were three important intercultural sensitivity dimensions: cultural engagement, respect to cultural differences and interaction enjoyment. This study contributes to the more understanding of intercultural dimensions and debates across the globe about intercultural issues. In addition, this study provides methodological contribution on the set of criteria to determine the scale of intercultural sensitivity.Â This study has further implication of the teaching and learning as one of the key elements on English curriculum. The study suggested that the research on wider participants can further enhance the sounding of this findings and provide overarching understanding of intercultural sensitivity.